Correlation of PROMIS Scores with the Various Classes of the New Classification System of Progressive Collapsing Foot Deformity - Seif El Masry; Grace DiGiovanni BS; Brittany M. Ammerman MD; Allison L. Boden MD; Jonathan Day MD; Joseph T. Nguyen MPH; Cesar de Cesar Netto MD, PhD; Scott J. Ellis MD (Foot & Ankle Orthopaedics)
Category: Other; Hindfoot Introduction/Purpose: The current classification system of progressive collapsing foot deformity (PCFD) is comprised of 5 classes that can occur simultaneously. Classes A-E indicate various deformities: hindfoot valgus, midfoot/forefoot abduction, forefoot varus/medial column instability, and ankle joint instability/valgus tilting in the ankle mortise, respectively. While the relationship between each of the PCFD deformities in the classification system to one another has been studied, to our knowledge, the correlation between the various classes and patient-reported outcomes has not been assessed. The purpose of this study was to evaluate whether the PCFD classification system is predictive of patient-reported outcomes and overall prognosis following surgery. The hypothesis was that patients with more severe deformity would have worse patient-reported outcomes. Methods: A retrospective review of prospectively collected data within an institutional registry was performed. We identified 74 patients aged 18 or older who were treated surgically for PCFD between October 2018 and October 2021 with preoperative, 1-year, and 2-year postoperative PROMIS scores. Chart review was performed to obtain demographic information and to confirm the surgical procedures completed. Using radiographs, weight-bearing computed tomography (WBCT), and office notes, patients were classified using the PCFD classification system. Patients were divided into two groups depending on whether subclasses D and/or E were present, indicating more severe deformity. Linear mixed models were used to assess longitudinal change in PROMIS scores between groups over time. Results: Patient demographic and classification characteristics are presented in Table 1. 47 patients were allocated to the Class D/E group and 27 patients were allocated to the No Class D/E group. Patients in the Class D/E group had worse pre-operative Global Physical Health (GPH) (p=0.018) and depression scores (p=0.012); however, post-operatively, there was only a difference in the PROMIS domain of Physical Function (PF) at both 1-Year (p=0.019) and 2-Year (p=0.038) time points (Table 2). There were no statistical differences between the two groups for any other domain at any timepoint (Table 2). Conclusion: Patients with more severe PCFD had clinically significant improvement in physical function at both 1- and 2-years post-operatively, but had worse outcomes compared to those with less severe deformity. The findings regarding preoperative GPH and depression suggest that while Class D/E patients did not perform as well functionally, they may be satisfied with their overall quality of life due to the similar scores postoperatively when compared to the patients with less severe deformity. Future studies are needed to better determine if the novel PCFD classification system is predictive of overall prognosis following surgery based on the various deformities present.